The Effect Of Self-Care Program On Hypertension Patients In The Islands - Sukarna, R Ade; Abilowo, Ashar (Oshada, 2024)
Hypertension is the leading cause of death from cardiovascular disease. Approximately 75% of the world's hypertensive population lives in low- and middle-income countries (LMICs). The results of the Basic Health Survey in Indonesia in 2018 show that the prevalence of hypertension has increased compared to 2013. The increase in patients with hypertension as a chronic disease requires independent self-care and routine monthly visits to health services. This study aims to determine the effect of self-management programs on blood pressure in hypertensive patients in the islands. The study was conducted in Belitung Island, Indonesia. The design of this study was quasi-experimental with pre-post test with control group. The sample was taken by convenience sampling technique with a total of 100 participants divided into 50 control groups and 50 intervention groups. Data were collected using self-care modules, questionnaire sheets, and blood pressure measured with a digital sphygmomanometer. Paired t-test and independent t-test were used for data analysis. Results of the study were collected at weeks 4 and 8. After 8 weeks of self-care with the provided modules, the results showed a significant relationship between mean blood pressure before and after the intervention